THE PROBLEMS OF WRITING RECOUNT ENCOUNTERED BY STUDENTS OF THE STATE JUNIOR HIGH SCHOOL 2 PURWOREJO IN THE ACADEMIC YEAR 2009/2010 (English Education Journal, 2011)
Writing is a skill for the students to express their ideas in written form thatinvolves the mastery of all elements in the target language: as grammar,content, organization, vocabulary, punctuation, spelling and mechanics. Itneeds a complex process. Consequently, the students may have difficultiesto do so.The objectives of my study are to find out how the communicativepurpose of a recount text written by the students is achieved, how recounttexts written in terms of functional stages, the features of lexico -grammatical problems, and to explain why the students write recount text inthe way they do. The problems of the study are therefore: how is thecommunicative purpose of recount texts written by the students of "SMP N"2 Purworejo?; how are recount texts written in terms of functional stages?;what are the features of lexico - grammatical problems faced by thestudents?; and, why do the students write recount texts in the way they do?The approach used in this study is qualitative.This study primarily dealswith the communicative purpose, functional stages and grammaticalproblems on writing recount made by the students of "SMP N "2Purworejo. The analysis result proved that the communicative purpose is toretell their past experience and they could write the functional stages onwriting recount well. Based on the data and the interview, I conclude thatthe 8th graders of "SMP N "2 Purworejo in the academic year 2009/2010had lexico-grammatical problems in writing recount. Those problemsoccurred because most of them made overgeneralization errors andthey had limited vocabulary.